It's Splitsville: Why Animal Ethics and Environmental Ethics Are Incompatible. (July 2019) - Faria, Catia; Paez, Eze
In this article, we claim that animal ethics and environmental ethics are incompatible ethical positions. This is because they have incompatible criteria of moral considerability and they have, at least in some cases, incompatible normative implications regarding the interests of sentient individuals. Moreover, we claim that environmentalist views lead to an insurmountable dilemma between inconsistency and implausibility and fail to properly account for the importance of wild animal suffering. From this it follows not only that (a) we can endorse one of the two views but not both at the same time but also that (b) we have overriding reasons to reject environmentalism and endorse some animal ethics view.